An Approach to Determine Effect of Crane Hook on Payload Sway. - Sulaiman, Shamsuddin; Ahmad, Desa; Abdul Aziz, Faieza; Safarzadeh, Daryoush; Majzoobi, Gholam Hossein (2011)
One of the factors which affects on the sway of payload is crane hook. For determination the relationship be-tween payload sway and hook peculiarities including mass and length, an approach was proposed based on the Lagrange equation to obtain equations of motion for a system with seven-degrees-of-freedom. A laboratory test by use of a special hook with adjustable mass and length was carried out to validate the results. Both theoretical and experimental outcomes confirmed the effect of hook on payload sway. Increasing the mass and length of hook will cause the pendulum motion of the payload to be suppressed in a short time